PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KARTU ARISAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMA NEGERI 11 PEKANBARU - Astuti, Eni; M Noer, Asmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The research aims to increase student learning achievement on the subject structure of atoms and the periodic system of elements in class XI science SMAN 11 Pekanbaru. This research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI IPA 3 as the experimental class and students of class XI IPA 4 as the control class. Experimental class is a class that is applied cooperative learning type Lottery Card model, while the control class was not. Data analysis technique used is the t-test. Based on analysis data tcount>ttable is 1,84 > 1,67, means that the application of model cooperative learning type lottery card can improve student achievement on the subject structure of atoms and the periodic system of elements in class XI science SMAN 11 Pekanbaru by category increase achievement (N-Gain) high at 0.72.Keywords: Learning Achievement, Cooperative type Lottery Card, Atomic Structure and Element of the Periodic System.